2015
DOI: 10.1016/j.tsf.2015.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Zr2Al3C4 thin films

Abstract: Zr2Al3C4 is an inherently nanolaminated carbide where layers of ZrC alternate with layers of Al3C2. Characterization of bulk samples has shown it has improved damage tolerance and oxidation resistance compared to its binary counterpart ZrC. Though a potential candidate for coatings applied for use in harsh environments, thin films of Zr2Al3C4 have not been reported. We have synthesized epitaxial Zr2Al3C4 thin films by pulsed cathodic arc deposition from three elemental cathodes, and have studied the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Generally speaking, as the intercalated Al layers increase, the formation energy of V Zr and V Al increases, while the formation energy of V C decreases. It is reported that the Zr–Al–C nanolaminates are the potential candidates for nuclear fuel cladding materials . A direct evaluation on the radiation resistance of the Zr–Al–C nanolaminates is difficult from the first‐principles calculation due to the complexity of the irradiation process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally speaking, as the intercalated Al layers increase, the formation energy of V Zr and V Al increases, while the formation energy of V C decreases. It is reported that the Zr–Al–C nanolaminates are the potential candidates for nuclear fuel cladding materials . A direct evaluation on the radiation resistance of the Zr–Al–C nanolaminates is difficult from the first‐principles calculation due to the complexity of the irradiation process.…”
Section: Resultsmentioning
confidence: 99%
“…For (ZrC) n Al 3 C 2 (n = 2, 3, 4), the Zr-C bond adjacent to the Al-C slab with the C atom intercalated in the Zr layers is the strongest, but the one with the C atom intercalated between the Zr layer and Al layer is the weakest. However, the situation for (ZrC) n Al 4 The available theoretical values for ZrC are listed in parentheses. (The atom sites are labeled in Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations